The Role of Carbon Risk Perception, Accountant Behavioral Compliance and Sustainability Mindset on the Accuracy of Carbon Performance Reporting - Gusti Meinar Girda Ariani; Syahrani Syahrani; Maria Yovita R Pandin; Amiartuti Kusmaningtyas (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the development and scientific relationship between carbon risk perception, behavioral compliance of accountants, and sustainability mindset on the accuracy of carbon performance reporting through a bibliometric approach. This study is driven by the increasing need for accurate carbon reporting amidst global demands for sustainability transparency, as well as the limited understanding of the role of behavioral and psychological factors of accountants in ensuring the reliability of carbon reports. Research data was obtained from two leading scientific databases, namely Scopus and Google Scholar, with the main keywords